Cheese rheology and texture - Gunasekaran, Sundaram, 1957- (CRC Press, 2003)
Cheese Rheology and Texture is the first reference to bring together the essential information on the rheological and textural properties of cheese and state-of-the-art measurement techniques. This comprehensive resource begins with an overview of cheesemaking technology and detailed descriptions of fundamental rheological test methods. Then it presents uniaxial testing and fracture mechanics, the theory and applications of linear viscoelastic methods (dynamic testing), and the nonlinear viscoelasticity of cheeses. The book focuses on mechanics in its examination of cheese texture, while it emphasizes measurement methods in its discussion of cheese meltability and stretchability. Finally it addresses the effects of various factors, such as the properties of milk, cheesemaking procedures, and post-manufacturing processes, on the functional properties of cheese. Summarizing the vast literature available on the subject, Cheese Rheology and Texture helps those in the dairy industry and in academia choose the proper technique to measure properties that directly relate to food applications and ensure that cheese in their formulations will function as intended.